Elevated risk of venous but not arterial thrombosis in Waldenström macroglobulinemia/lymphoplasmacytic lymphoma. (6th October 2014) - Hultcrantz, M.; Pfeiffer, R. M.; Björkholm, M.; Goldin, L. R.; Turesson, I.; Schulman, S.; Landgren, O.; Kristinsson, S. Y.
Summary Background Many malignancies, including multiple myeloma and its precursor, monoclonal gammopathy of unknown significant, are associated with an elevated risk of thromboembolism. There is limited information on the risk of thrombosis in patients with Waldenström macroglobulinemia (WM) and lymphoplasmacytic lymphoma (LPL). Objectives To assess the risk of venous and arterial thrombosis in WM/LPL patients in a large population‐based cohort study in Sweden. Patients/methods A total of 2190 patients with WM/LPL and 8086 matched controls were identified through Swedish registers between 1987 and 2005. Information on occurrence of venous and arterial thrombosis after the diagnosis of WM/LPL was obtained through the centralized Swedish Patient Register, with follow‐up to 2006. Cox regression models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results Patients with WM/LPL had a significantly increased risk of venous thrombosis and the highest risk was observed during the first year following diagnosis (HR = 4.0, 95% CI 2.5–6.4). The risk was significantly elevated 5 (HR = 2.3, 95% CI 1.7–3.0) and 10 years after diagnosis (HR = 2.0, 95% CI 1.6–2.5). There was no increased risk of arterial thrombosis during any period of follow‐up time (10‐year HR = 1.0, 95% CI 0.9–1.1). Conclusions Venous thrombosis is a significant cause of morbidity in patients with WM/LPL. The potential role of thromboprophylaxis in WM/LPL, especially during the first year after diagnosis and in patients treated with thrombogenic agents, needs to be assessed to further improve outcome in WM/LPL patients.